Long term high glucose exposure induces premature senescence in retinal endothelial cells - Bertelli, Pietro Maria; Pedrini, Edoardo; Hughes, David; McDonnell, Shannon; Pathak, Varun; Peixoto, Elisa; Guduric-Fuchs, Jasenka; Stitt, Alan W; Medina, Reinhold J. (Frontiers in Physiology, 2022)
Purpose: Features of cellular senescence have been described in diabetic retinal vasculature. The aim of this study was to investigate how the high glucose microenvironment impacts on the senescence program of retinal endothelial cells. Methods: Human retinal microvascular endothelial cells were cultured under control and high glucose conditions of 5mM and 25mM D-glucose, respectively. Isomer L-glucose was used as the osmotic control. Cells were counted using CASY technology until they reached their Hayflick limit. Senescence-associated β-Galactosidase was used to identify senescent cells. Endothelial cell functionality was evaluated by the clonogenic, 3D tube formation, and barrier formation assays. Cell metabolism was characterized using the Seahorse Bioanalyzer. Gene expression analysis was performed by bulk RNA sequencing. Retinal tissues from db/db and db/+ mice were evaluated for the presence of senescent cells. Publicly available scRNA-sequencing data for retinas from Akimba and control mice was used for gene set enrichment analysis. Results: Long term exposure to 25mM D-Glucose accelerated the establishment of cellular senescence in human retinal endothelial cells when compared to 5mM D-glucose and osmotic controls. This was shown from 4 weeks, by a significant slower growth, higher percentages of cells positive for senescence-associated β-galactosidase, an increase in cell size, and lower expression of pRb and HMGB2. These senescence features were associated with decreased clonogenic capacity, diminished tubulogenicity, and impaired barrier function. Long term high glucose-cultured cells exhibited diminished glycolysis, with lower protein expression of GLUT1, GLUT3, and PFKFB3. Transcriptomic analysis, after 4 weeks of culture, identified downregulation of ALDOC, PFKL, and TPI1, in cells cultured with 25mM D-glucose when compared to controls. Db/db mice retinas showed a significant decrease in vascular density in the intermediate and deep retinal plexuses, when compared to db/+ mice. Senescent endothelial cells within the db/db retinal vasculature were identified by senescence-associated β-galactosidase staining. Analysis of single cell transcriptomics data for the Akimba mouse retina highlighted an enrichment of senescence and SASP gene signatures when compared to control mice. Conclusion: A diabetic-like microenvironment of 25mM D-glucose was sufficient to accelerate the establishment of cellular senescence in human retinal microvascular endothelial cells.